Brachial artery endothelial function is stable across the morning in young men. Issue 1 (December 2015) - Thosar, Saurabh; Wiggins, Chad; Shea, Steven; Wallace, Janet
Abstract Background The morning hours are associated with increased cardiovascular (CV) risk, and vascular endothelial function (VEF) is a strong predictor of CV disease. A diurnal rhythm in VEF has been established but the morning variation in VEF is not well-documented. Thus, we tested if VEF is impaired across the vulnerable morning period. Methods After overnight fasts, eight healthy men (age 26.3 ± 3 yr) underwent assessments of VEF under standardized testing conditions every 2 h from 0700 to 1300 h on two separate days. VEF was estimated following 5 min brachial artery occlusions by hyperemic flow-mediated dilation (FMD). Results There was no significant change in FMD or hyperemic shear stimulus across the 6 h vulnerable period on either day, despite changes in physical activity and meals across these periods. Conclusion In this healthy group of young men, VEF is stable across the vulnerable morning period when typical behaviors occurred (breakfast and physical activity). Future research should focus on the roles of sleep, physical inactivity during sleep and endogenous circadian rhythm in VEF.